Curved radiators in the near-field and far-field zones of observation - Gorobets, N. N.; Trivaylo, A. V. (Видавництво Національного університету "Львівська політехніка", 2009)
In approximation of the given current distribution it has been suggested a solution considering the influence of the circular loop antenna curvature and elementary radiator curvature upon their directional characteristics. On the basis of potential Hertz technique the expressions for calculating al the components of electromagnetic radiation fields of wire loop antennas, stimulated by the running wave of the current, and curved dipole in Spherical and Decart coordinate systems in the near-field zone have been derived. It has been shown that wave processes near by the examined radiators are distinguished by great gradients of amplitudes of the electromagnetic fields.
Keywords: curved dipole; circular loop antenna; near-field-zone; electromagnetic waves